Can vitamin D supplementation be dangerous? 25-Hydroxyvitamin D and 1,25-hydroxyvitamin D concentration in healthy population and primary hyperparathyroidism: a single-center experience and literature review - Obołończyk, Łukasz; Berendt-Obołończyk, Monika; Sworczak, Krzysztof; Karwacka-Bujak, Izabela; Majerowska, Ewa; Renke, Marcin (Frontiers in Endocrinology, 2025)
Primary hyperparathyroidism (PHPT) is an excessive secretion of PTH caused by a defect in parathyroid cells, insensitive to the suppressive effects of hypercalcemia. The effect of 25-hydroxyvitamin D3 (25-OH-D) and skeletal and extra-skeletal conditions is well known, but the impact of 25-OH-D and 1,25-OH-D in the pathogenesis of primary hyperparathyroidism (PHPT) is still poorly researched. The study group (SG) consists of 85 patients with diagnosed PHPT. The control group (CG) consists of 51 patients without calcium-phosphate imbalance. The SG was divided into two subgroups: SG1 (patients with PHPT qualified for conservative management) and SG2 (patients who are qualified for surgical treatment). Serum PTH, calcium and phosphates concentration were assessed as well as the concentration of 25-OH-D and 1,25-OH-D. The ratio of 1,25-OH-D to 25-OH-D was introduced: vitamin D activation ratio (VD-AR). The median concentration of 25-OH-D3: 30,00 ng/mL in CG, 32,75 ng/ml in SG1 and 27,6 ng/mL in SG2. The highest 1,25-OH-D3 median concentration was found among patients in SG2 (91,1 pg/mL) lower in SG1 (64,05 pg/mL) and the lowest in CG (46,20 pg/mL). VD-AR was highest in SG2 as well, with median 3,32. Results given prove the statistically significant differences between the medians of 1,25-OH-D and VD-AR between pairs of all groups (e.g. SG1 vs. SG2; SG1 vs. CG etc.). In the logit model for calcium, the structural parameter for the VD-AR was statistically significant-the higher the value of VD-AR the greater the probability of hypercalcemia above 11 mg/dL (74.1%). In the logit model for indication for parathyroidectomy, the structural parameter for the VD-AR and iPTH was statistically significant at 0.05 significance level, which means that higher value of VD-AR the greater probability of surgery and independently the higher serum concentration of iPTH the greater probability of surgery as well (72.9%) To conclude, 1,25-OH-D serum concentration and VD-AR are significantly higher in PHPT patients than in the healthy population. 1,25-OH-D serum concentration and VD-AR are significantly higher in PHPT patients qualified to surgery than qualified to conservative treatment. Moreover, higher value of VD-AR makes greater probability of hypercalcemia above 11 mg/dL. We suggest VD-AR cut-off 3.3 as clinically relevant.